2010
DOI: 10.1111/j.1542-4758.2010.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single hemodialysis session on inflammatory markers

Abstract: Inflammation is a common feature of end-stage renal disease. Although there is evidence for hemodialysis (HD)-induced inflammatory process, the effect of a dialysis session on changes in inflammatory markers is still unclear. Seventeen patients of end-stage renal disease on maintenance HD along with 20 age-matched and sex-matched healthy controls were recruited after informed consent. C-reactive protein (CRP) and lipoprotein-associated phospholipase A2 (LpPLA2) activity were measured in the study and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…18 Two previous studies in uremic patients undergoing various dialysis procedures demonstrated that PAF-AH activity in the plasma of patients with stage 3-4 chronic kidney disease was significantly higher than control subjects. 19,20 In a recent study, Bitla et al 6 reported that Lp-PLA2 activity is increased at the end of dialysis session and suggested that HD therapy produces an increase in Lp-PLA2 activity. In contrast, Milionis et al 19 demonstrated that PAF-AH activity was not different before and after the dialysis procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Two previous studies in uremic patients undergoing various dialysis procedures demonstrated that PAF-AH activity in the plasma of patients with stage 3-4 chronic kidney disease was significantly higher than control subjects. 19,20 In a recent study, Bitla et al 6 reported that Lp-PLA2 activity is increased at the end of dialysis session and suggested that HD therapy produces an increase in Lp-PLA2 activity. In contrast, Milionis et al 19 demonstrated that PAF-AH activity was not different before and after the dialysis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a marker of systemic inflammation, while Lp-PLA2 represents a specific marker for local vascular inflammation and endothelial dysfunction, suggesting that both have different pathophysiological mechanisms and providing a plausible explanation for not finding a correlation between these two markers. 6 Dialysis-induced local inflammation might be able to increase the Lp-PLA2 production as well as CRP production. CRP might not be the ideal marker to study inflammatory changes as a result of dialysis; however, Lp-PLA2 serves as a better biochemical marker to determine the effects of dialysis on inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Furthermore, chronic hemodialysis (HD) can stimulate the intracellular pattern of inflammatory mediators. 1,3 As a result, the development of a chronic inflammatory state is associated with certain conditions such as muscle atrophy, malnutrition, chronic infections and atherosclerotic processes, and major causes of morbidity and mortality. 4 Cytokines are glycoproteins with low molecular weight, secreted in response to antigens, danger signals or others chemical messengers and that regulate many immunological aspects across pro-or anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%